Mobilitas, Negosiasi dan Transisi Perempuan Muda di Jawa Tengah - Oki Rahadianto Sutopo; Rani Dwi Putri (Universitas Gadjah Mada, 2019)
Post-Fordism is a relevant context in framing the issue of school to work transition faced by the young generation. In this era, the labor market not only requires energy, but also more specific skills. In addition, rapid and massive social change in the Post-Fordism era requires young people to compete at the local, national and global level. On the other hand, young people are faced with the fact that the distribution of capital has never been equally distributed in every social space. Thus, mobility is one of the important strategies for young generation as an effort to accumulate cultural, social, economic and symbolic capital. This study uses qualitative methods with observation and in-depth interviews as data collection techniques. Through the narratives of 4 young women in Central Java, this study concludes that they must reflexively strategize under particular conditions where social inequality is manifested in the spatial dimension, while at the same time intersects with gender and social class. From family support and opportunities for educational scholarships, two young women utilize mobilities to respond social change towards a new economy amid limited amount of capital accumulation. Two other young women had to to lose their opportunity to achieve upward class mobility. Thus structural and cultural obstacles as women and social class, make it difficult for two young women to upgrade their own capital; thus social change towards Post-Fordism tends to be a threat rather than an opportunity.